2022
DOI: 10.1073/pnas.2204515119
|View full text |Cite
|
Sign up to set email alerts
|

Spinal neuropeptide Y Y1 receptor-expressing neurons are a pharmacotherapeutic target for the alleviation of neuropathic pain

Abstract: Peripheral nerve injury sensitizes a complex network of spinal cord dorsal horn (DH) neurons to produce allodynia and neuropathic pain. The identification of a druggable target within this network has remained elusive, but a promising candidate is the neuropeptide Y (NPY) Y1 receptor-expressing interneuron (Y1-IN) population. We report that spared nerve injury (SNI) enhanced the excitability of Y1-INs and elicited allodynia (mechanical and cold hypersensitivity) and affective pain. Similarly, chemogenetic or o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 110 publications
0
34
0
Order By: Relevance
“…As expected, we observed no mCherry-labelled cells in the contra- or ipsilateral L4 or L5 DRG of these mice (data not shown). Spinal NPY signalling has been implicated in the suppression of neuropathic pain through inhibition of NPY Y1 receptor (Y1R)-expressing excitatory interneurons in the dorsal horn 29, 43, 44 . Therefore the suppression of neuropathic hypersensitivity that we observed during chemogenetic activation of NPY-INs could be due to GABAergic transmission, NPY signalling, or a combination of both.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, we observed no mCherry-labelled cells in the contra- or ipsilateral L4 or L5 DRG of these mice (data not shown). Spinal NPY signalling has been implicated in the suppression of neuropathic pain through inhibition of NPY Y1 receptor (Y1R)-expressing excitatory interneurons in the dorsal horn 29, 43, 44 . Therefore the suppression of neuropathic hypersensitivity that we observed during chemogenetic activation of NPY-INs could be due to GABAergic transmission, NPY signalling, or a combination of both.…”
Section: Resultsmentioning
confidence: 99%
“…Since the optogenetic activation of NPY1R + JNC neurons trigger expiratory reflexes in mice (1) and NPY1R activation impacts pain and itching reflexes (34)(35)(36)(37)(38)(39)(40)(41)(42), we sought to test how it would impact airway nociceptor neuron function. Interestingly, we found that along with airway inflammation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…NPY1R is a Gi-coupled receptor (44) and its activation in DRG nociceptor neurons promotes either analgesia or noxious hypersensitivity (34)(35)(36)(37)(38)(39)(40)(41)(42). Given this discrepancy we set out to address how NPY-NPY1R modulates cultured JNC nociceptor neuron sensitivity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral sensitization is due to a sustained peripheral stimulation that makes primary sensory neurons undergo altered plasticity and become abnormally excitable [ 4 , 5 ]. Neurons undergo epigenetic changes to respond to harmful stimulation [ 6 ].…”
Section: Introductionmentioning
confidence: 99%